Investigation of Nonlinear Optical Properties of NiO Nanoparticles using the Z-Scan Technique - Seidalilir, Zahra; Rasheed, Sabreen A.; Humud, Hammad R. (Iraqi Journal of Science, 2024)
In this research, linear and nonlinear optical properties of NiO nanoparticles (NPs) dissolved in ethanol were investigated. Linear optical characteristics of NiO NPs were studied using a UV-Vis spectrophotometer. The linear absorption coefficient (α0) was 0.88 and 0.57 cm-1 at 405 and 532 nm wavelengths, respectively. The band gap energy rose from 3.56 eV for a sample with a 10-7 g/ml concentration to 3.92 eV for the 10-3 g/ml concentration sample. Using the Z-scan technique, the nonlinear optical characteristics of the NPs were investigated. Two continuous wave laser diodes with 405 and 532 nm wavelengths and different powers were used. The Z-scan system with a closed aperture revealed that NiO NPs have a negative n2 (self-defocusing effect) at various laser powers. n2 increases as the power of the laser increases. The value of n2 was found to be 0.51×10-4 cm2/mW at a wavelength of 405 nm and a power of 0.33 mW. It improved as the laser power increased, reaching a maximum of 0.64×10-4 cm2/mW at a laser power of 1.51 mW. For the laser with a wavelength of 532 nm, the n2 value was 0.27×10-4 cm2/mW for a laser power of 1.01 mW. This value increased to 0.76×10-4 cm2/mW when the laser power increased to 6.2 mW. As measured by the Z-scan system with an open aperture, NiO NPs have a nonlinear absorption coefficient and display a two-photon absorption behavior.